1998
DOI: 10.1016/s0006-3495(98)77758-6
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of β2-Integrin and L-Selectin Bonding during Neutrophil Aggregation in Shear Flow

Abstract: Activated neutrophils aggregate in a shear field via bonding of L-selectin to P-selectin glycoprotein ligand-1 (PSGL-1) followed by a more stable bonding of LFA-1 (CD11a/CD18) to intercellular adhesion molecule 3 (ICAM-3) and Mac-1 (CD11b/CD18) to an unknown counter receptor. Assuming that the Mac-1 counter receptor is ICAM-3-like in strength and number, rate processes were deconvoluted from neutrophil homoaggregation data for shear rates (G) of 100-3000 s-1 with a two-body hydrodynamic collision model (. Biop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0
4

Year Published

2002
2002
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 40 publications
1
26
0
4
Order By: Relevance
“…49 Previous work has predicted the effects of leukocyte deformability on adhesion kinetics, 18,39 as well as the kinetics of integrin and L-selectin mediated neutrophil aggregation under flow. 107 All of these computational models are highly detailed and mechanistically informative, but they neglect the overall spatial and temporal dynamics within entire tissues. Thus, our model fills a critical gap and provides a tool to interrogate the individual and combined effects of molecules, cell behaviors, and mechanical forces.…”
Section: Discussionmentioning
confidence: 99%
“…49 Previous work has predicted the effects of leukocyte deformability on adhesion kinetics, 18,39 as well as the kinetics of integrin and L-selectin mediated neutrophil aggregation under flow. 107 All of these computational models are highly detailed and mechanistically informative, but they neglect the overall spatial and temporal dynamics within entire tissues. Thus, our model fills a critical gap and provides a tool to interrogate the individual and combined effects of molecules, cell behaviors, and mechanical forces.…”
Section: Discussionmentioning
confidence: 99%
“…24,52 In those pioneering work, a deterministic kinetic model was proposed, by setting a critical number of bonds to support stable formation of cell aggregates, to predict the collision efficiency and reverse rate of GPIIb/IIIa-fibrinogen binding for platelet aggregation, 45 or b 2 -integrin-ICAM-3 and L-selectin-PSGL-1 (P-selectin glycoprotein ligand 1) binding for neutrophil aggregation. 46 Recent evidence indicated that 2D receptor-ligand binding mediated by a small number of bonds is no longer a deterministic but a stochastic process. 5,7,53 To extract the molecular kinetic parameters from the time-dependent cell aggregation and disaggregation, we previously developed a probabilistic kinetic model to predict shear-induced doublet formations and breakages of red blood cells and of latex beads crossed-linked by antigen-antibody bonds.…”
Section: Introductionmentioning
confidence: 99%
“…Both PSGL-1 and L-selectin molecules are concentrated on tips of PMN microvilli (Puri et al 1997) (see Table 1 for their respective numbers). Homotypic PMN aggregation in vitro or in vivo is supported by multiple bonds between ( Tandon and Diamond 1998) L mv Length of microvillus 0.35 µm ( Shao et al 1998) N mv No. of microvilli/cell 252 (Chen and Springer 1999) N R No.…”
Section: Introductionmentioning
confidence: 99%